Public Space in the Peri-Urban Settlements of Sarajevo. A Project for the Mahala of Širokača - Richard Lee PERAGINE (Territorial Identity and Development, 2019)
This paper outlines a project for the reactivation of the peri-urban settlements, known as mahalas, which surround Sarajevo, Bosnia & Herzegovina. For historical, social and economic reasons, the growth of the mahalas has been largely informal and uncontrolled by planning regulations with the result that today they exemplify both the dysfunctions and the potentials of spontaneous and uncontrolled urban expansion. The absence of adequate urban planning, both previous to and following a period of armed conflict, together with a failed process of social reconstruction, has left the mahalas in a state of physical abandon and without a shared identity and memory of place. Lacking public infrastructure, they are cut off from the central parts of the city and from the services these provide. In terms of natural conditions, due to the steep slopes and the nature of the bedrock the area is vulnerableto landslides. A failure to address this problem has resulted in the construction of buildings in high-risk locations. This study examines a rethinkingof the Širokača mahala. It identifies four strategic objectives: the reduction of landslide risk; the reconnection, both physical and psychological, with the city; the reactivation of the mahala through the provision of public spaces and services; the provision of new homes for the recollocation of the weakest elements of the population as part of the wider national programme for the recollocation of internally displaced people (IDPs).The project finds its guiding principle in a scattered approach consisting of a series of small scale interventions that together create a pathway of facilities which in turn can be reproduced at the macro-level of an urban system. Bottom-up initiatives and practices of urban resilience, latent potential of Sarajevo, are proposed in order to foster a process of physical and social reconciliation within the community.